Equilibrium profile development in graded deep-water slopes: Eocene, Eastern Turkey - Cronin, BT; Hartley, AJ; Celik, H; Hurst, A; Türkmen, I; Kerey, E (Geological Soc Publ House, 2000)
Recently published models for deep marine slopes provide a framework for understanding the sedimentary architecture and geometries of major correlative surfaces in this environment. These models use concepts which include: (i) the development of erosional and unconformable onlapping relationships in a slope-to-basin setting by processes other than changes in relative sea-level (e.g. earthquake induced gravity Rows), (ii) the definition of genetic facies associations and (iii) the development of base-of-slope systems by repeated mass-wasting in order to establish an equilibrium slope profile. These models are based primarily on seismic data from present-day slopes or numerical simulation, and have not been tested in the field. An example from Turkey of a progradational Eocene basin-to-slope transition is presented to test these models. We found that most mass-wasting occurs at the top and not base of the slope, that this is likely to be earthquake-induced rather than related to changes in relative sea-level, and that seafloor topography continues to control sand transportation pathways and mass-wasting throughout slope apron deposition.
Keywords: Turkey; turbidites; deep-water environment; slopes; mass; movements